2017
DOI: 10.1530/ec-17-0257
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone has the same cardiovascular risk profile as hydrocortisone in glucocorticoid replacement

Abstract: IntroductionPatients who need glucocorticoid replacement in both primary and secondary adrenal insufficiency (AI) have the choice of either once-daily prednisolone or thrice-daily hydrocortisone. A recent European study found no difference between prednisolone and hydrocortisone users in several markers including glucose, weight, body mass index, systolic and diastolic blood pressure and waist circumference, although an increase in cholesterol and low-density lipoprotein (LDL) was suggested in a subgroup of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…25 It is however clear that previously used doses have been excessive and 3-4 mg once daily is sufficient replacement in most patients. 26,27 Currently, there are two NIHR adopted studies actively recruiting, comparing lowdose prednisolone with standard regimens of hydrocortisone. 28,29 Low-dose prednisolone has been shown to be superior in reducing androgens, 17-hydroxy progesterone and improving growth velocity in patients with congenital adrenal hyperplasia compared to thricedaily hydrocortisone.…”
Section: Oral Preparations Of Glucocorticoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 It is however clear that previously used doses have been excessive and 3-4 mg once daily is sufficient replacement in most patients. 26,27 Currently, there are two NIHR adopted studies actively recruiting, comparing lowdose prednisolone with standard regimens of hydrocortisone. 28,29 Low-dose prednisolone has been shown to be superior in reducing androgens, 17-hydroxy progesterone and improving growth velocity in patients with congenital adrenal hyperplasia compared to thricedaily hydrocortisone.…”
Section: Oral Preparations Of Glucocorticoidsmentioning
confidence: 99%
“…Further data from a prospective observational study in Germany recorded the frequency of crises experienced by patients on different treatment regimens, and showed that the proportion of patients on prednisolone experiencing a crisis was not greater than expected . It is however clear that previously used doses have been excessive and 3‐4 mg once daily is sufficient replacement in most patients . Currently, there are two NIHR adopted studies actively recruiting, comparing low‐dose prednisolone with standard regimens of hydrocortisone .…”
Section: Introductionmentioning
confidence: 99%
“…This patient's experience confirms recent evidence that the dose required for adequate replacement is far less than the 7.5 mg traditionally quoted. If prednisolone is to be used as replacement glucocorticoid, we recommend a starting dose of 3‐4 mg daily …”
Section: Case Reportmentioning
confidence: 99%
“…There is evidence that it is at least not inferior to the currently most widely used therapy, thrice-daily hydrocortisone 2 .…”
mentioning
confidence: 99%